Transformation of Traditional Values in Urban Society: Humanities Study of Urban Culture - Nuraedah, Nuraedah (PT. Anagata Sembagi Education, 2025)
Urban culture reflects the complex dynamics that occur in urban areas due to the interaction between traditional values, modernity, globalization, and technology. This study aims to analyze urban culture through a humanities approach, focusing on the transformation of traditional values, the influence of technology and digital media, and the construction of cultural identity in diverse urban communities. This study uses a literature study method, examining various theories and relevant empirical findings to understand the relationship between social change and cultural development in big cities. The results of the study show that urban communities face challenges in maintaining traditions amidst modern lifestyles that tend to be individualistic. Technology, on the one hand, supports the preservation of culture through digital media, but on the other hand has the potential to create social alienation and cultural commodification. In addition, changes in urban spatial planning such as the development of business areas and the reduction of community space affect the pattern of social interaction in society. However, the diversity of urban communities and their ability to adapt allows the creation of new hybrid cultural forms, combining traditional and modern elements. This study emphasizes the importance of a humanities approach in understanding urban culture to support the development of inclusive, sustainable policies based on the preservation of local values, so that urban cultural identity can continue to develop without losing its authenticity.